Allostatic Load and Adverse Pregnancy Outcomes. Issue 5 (May 2023) - Lueth, Amir J.; Allshouse, Amanda A.; Blue, Nathan M.; Grobman, William A.; Levine, Lisa D.; Simhan, Hyagriv N.; Kim, Jin Kyung; Johnson, Jasmine; Wilson, Fernando A.; Murtaugh, Maureen; Silver, Robert M.
ABSTRACT: Approximately one-fourth of pregnancies experience adverse pregnancy outcomes, such as hypertensive disorders of pregnancy (HDPs), preterm birth, stillbirth, and small-for-gestational age (SGA) neonates. Although an uncertain pathophysiology leading to these outcomes of pregnancy is understood, a major contributing factor may be cumulative stress. Chronic wear and tear on the adaptive system of the body, as well as chronic stress exposure, can be assessed via allostatic load. Chronic stress hailing from circumstances such as food or housing insecurity, racism, unemployment, or a combination of these may contribute to the racial and ethnic disparities observed in pregnancy outcomes. This study aimed to assess the relationship between the allostatic load and adverse pregnancy outcomes, while hypothesizing that higher odds of adverse pregnancy outcomes are directly associated with higher allostatic loads. Second, the authors hypothesized that a significant portion of racial and ethnic disparities in adverse pregnancy outcomes will be accounted for with high allostatic loads. The primary outcome was a composite adverse pregnancy outcome: HDPs, SGA, preterm birth, and stillbirth. Between October 2010 and September 2013, the nuMoM2b study (Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-Be) enrolled 10, 038 nulliparous individuals with singleton pregnancies. Eligible individuals were nulliparous, had a viable single gestation with an estimated gestational age of 6 0/7 and 13 6/7 weeks, and intended delivery at a participating clinical site. Exclusionary criteria were as follows: unable to provide informed consent, age younger than 13 years, planned termination of pregnancy, 3 or more prior pregnancy losses, fetal malformations or aneuploidy upon enrollment, or having a donor ovum pregnancy. Included within the study were 3 study visits during pregnancy and a final visit at delivery. Baseline clinical assessments, standardized questionnaires by trained chart abstracts, and medical record abstraction were used to ascertain maternal characteristics. Assessment of urine and serum collected between 6 and 14 weeks granted insight into allostatic load biomarkers. A total of 4266 pregnant individuals were included in the primary analysis, with high allostatic load being identified in 35% of the population (≥4 biomarkers in the worst quartile). Some 1171 individuals (27.5%) were identified to have adverse pregnancy outcomes: 386 preterm births (8.6%), 586 HDPs (14.0%), 12 stillbirths (0.3%), and 449 SGA neonates (11%). Adverse pregnancy outcomes occurred in the following numbers: 1 adverse outcome for 967 individuals, 2 for 165, 3 for 38, and 1 for all 4. High allostatic load held significant association with composite adverse pregnancy outcome, whereas HDPs differed by self-reported race. After adjustment for maternal age, gravidity, smoking, bleeding in the first trimester, and health insurance, high allostatic load was associated with the composite adverse pregnancy outcome (adjusted odds ratio [aOR], 1.5; 95% confidence interval [CI], 1.3–1.7) and hypertensive disorders (aOR, 2.5; 95% CI, 2.0–2.9), but not preterm birth or SGA. High allostatic load only partially mediated the association between self-reported race and adverse pregnancy outcomes. The association between allostatic load and hypertensive disorders differed by self-reported race, but it did not differ for the composite adverse pregnancy outcome, preterm birth, or SGA. Limitations of the study included the small number of stillbirths. Furthermore, the study used the 10-factor allostatic load index and did not assess additional cardiovascular and metabolic indicators in the broader allostatic load index. In addition, the cohort only included nulliparous individuals with tertiary care center access, which is not necessarily generalizable to other populations. Strengths of the study included its use of a large, well-characterized prospective cohort, as well as equal weighing of allostatic load biomarkers and a study population that was racially, ethnically, and geographically diverse. In conclusion, the study indicates that early-pregnancy high allostatic loads are associated with subsequent adverse pregnancy outcomes (HDPs in particular). Allostatic load was also a partial mediator between adverse pregnancy outcomes and race. Further evaluation of components of chronic stress and allostatic load as potentially modifiable risk factors is supported by these findings as a means of improving pregnancy outcomes via these potentially modifiable risk factors.